Hubungan Antara Konsep Diri dan Dukungan Orang Tua Dengan Kematangan Karier Pada Siswa SMA - Fatmasari, Dhian; , Dra. Partini, M.Si (2016)
Maturity in career has been integrated with the adolescent task. If the career maturity does not reach properly upon the stage of development, the individual may have an obstacle in passing through the next stage of development. Career maturity influenced by several factors, including self-concept and parental support. The purpose of this research was to determine the relationship of self-concept and parental support toward career maturity of high school students; the relationship of self-concept toward career maturity of high school students; and the relationship of parental support toward career maturity of high school students. The method applied in this study was correlational research. Subjecs in this research were 102 (M= 41, F= 61) of high school students grade XI, around 15-18 years old, and the sample was taken by using quota sampling technique. The instruments used were career maturity scale, self-concept scale, and parental support scale. The data were analyzed by using multiple regression analysis techniques. Based on the analysis of this research, obtained result (a) There is a high significant relationship of self-concept and parental support toward career maturity (r= 0,699; p=0,00), (b) There is a high significant positive relationship between self-concept toward career maturity (r= 0,682; p= 0,00), (c) There is a high significant positive relationship between parental support toward career maturity (r= 0,533; p=0,00), (d) Self concept and parental support has contributed to career maturity with (R²=0,488), (e) Self concept has contributed to career maturiy with (R²=0,465), (f) Parental support has contributed to career maturity with (R²=0,284). Those three variable, career maturity, self-concept, and parental support have high categorization. The result of this research has implied the importance of self concept and parental support toward career maturity. The result will be discuss in this publication article.